2004
DOI: 10.1161/01.str.0000130512.81212.a2
|View full text |Cite
|
Sign up to set email alerts
|

Is Elevated Mean Platelet Volume Associated With a Worse Outcome in Patients With Acute Ischemic Cerebrovascular Events?

Abstract: Background and Purpose-Increased mean platelet volume (MPV), indicating higher platelet reactivity, is associated with an increased risk of myocardial infarction. Higher levels of MPV have been found in patients with acute ischemic stroke than in control subjects. Data from smaller studies regarding an association between MPV and stroke severity and outcome have been controversial. If such an association exists, MPV might help to identify patients at increased risk of a severe course of acute cerebrovascular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
232
3
19

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(266 citation statements)
references
References 24 publications
(22 reference statements)
12
232
3
19
Order By: Relevance
“…Thus, platelets exhibit hyper-responsiveness to ADP-or collagen-induced aggregation (1). Various studies reported that increased levels of MPV is an independent risk factor for arterial thrombotic events such as myocardial infarction and cerebral thromboembolism (2)(3)(4)(5). The patients with diabetes mellitus are at increased risk of macrovascular and microvascular complications.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, platelets exhibit hyper-responsiveness to ADP-or collagen-induced aggregation (1). Various studies reported that increased levels of MPV is an independent risk factor for arterial thrombotic events such as myocardial infarction and cerebral thromboembolism (2)(3)(4)(5). The patients with diabetes mellitus are at increased risk of macrovascular and microvascular complications.…”
Section: Introductionmentioning
confidence: 99%
“…15 An increased level of MPV was found to be related to various pathological conditions, including cardiovascular and cerebrovascular disorders, and deep venous thrombosis. [46][47][48] MPV was also investigated in some studies related to otolaryngological pathologies. Poorey et al reported an increased level of MPV due to chronic nasal obstruction in patients with deviated nasal septum.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as the technology used, variable pre-analytical effects of anticoagulants, temperature, and time of storage of the material all cause interferences when determining the MPV (GULATI et al, 2002;VOGELAAR et al, 2002). Using sodium citrate as an anticoagulant retains the platelets with a spherical shape, which could increase the MPV (MACEY et al, 2002;GREISENEGGER et al, 2004). Bulky and aggregate platelets have higher MPV values and decreased counts (RACCHI; RAPEZZI, 2001;BAIN;PATH, 2005).…”
Section: Daysmentioning
confidence: 99%